Implementation of Teacher and Peer Feedback in Writing Hortatory Exposition Text - Putri Lasminiar (Institut Agama Islam Negeri Madura, 2020)
Feedback from teacher and peer is doubted by experts to be implemented in the students’ writing process because of students’ preference in teacher feedback and students’ lack of ability to give feedback. Therefore, the purpose of this study was to investigate the implementation of teacher and peer feedback in the eleventh graders of SMAN 5 Malang in writing hortatory exposition texts. It is Collaborative Classroom Action Research (CAR) and the data were obtained through questionnaires, interview guides, observation checklist, field notes, and students’ writing assignments. The results showed that the implementation of teacher and peer feedback improved the students’ ability in writing hortatory exposition texts especially in the relating thesis statement, argument(s), and recommendation into one another. In terms of content, organization, language use, and mechanic, there were more than 75% of 32 students that could reach score at least 3 (the minimum score). The result also revealed that teacher and peer feedback could create students to become critical and independent learners